2007
DOI: 10.1136/aim.25.3.80
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Frequency and Duration of Electroacupuncture Stimulation on Carrageenan-Induced Hyperalgesia

Abstract: Objective Although electroacupuncture (EA) therapy is used to relieve various kinds of pain, the optimal frequency and duration of EA remain unclear. We investigated the effect of varying frequency and duration of EA during hyperalgesia elicited by carrageenan-induced inflammation. Methods Carrageenan was administered by subcutaneous intraplantar injection to induce inflammation. Nociceptive thresholds were measured using the paw pressure threshold (PPT) (Randall-Selitto Test). EA was applied at 3, 15, or 100H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
11
1
1
Order By: Relevance
“…The analgesic durations of the three different frequencies were significantly longer than that of previous studies with uninjured animal models, which showed only a short duration (20-60 min) of acupuncture analgesia [34][35][36]. However, several other reports have showed that acupuncture produces long-term therapeutic pain relief lasting for hours or even days in animals with inflammatory conditions [27,28,33,38]. One possible explanation is that the EA treatments were applied under mild anesthesia with uninjured animal models.…”
Section: Accepted Manuscriptcontrasting
confidence: 55%
“…The analgesic durations of the three different frequencies were significantly longer than that of previous studies with uninjured animal models, which showed only a short duration (20-60 min) of acupuncture analgesia [34][35][36]. However, several other reports have showed that acupuncture produces long-term therapeutic pain relief lasting for hours or even days in animals with inflammatory conditions [27,28,33,38]. One possible explanation is that the EA treatments were applied under mild anesthesia with uninjured animal models.…”
Section: Accepted Manuscriptcontrasting
confidence: 55%
“…Several randomised controlled trials (RCTs) have investigated the effects of acupuncture for the treatment of shoulder pain, with different combinations of acupuncture points, treatment protocols and methods of needle stimulation, [4][5][6][7][8][9][10][11][12][13][14] all of which potentially influence the therapeutic outcome of acupuncture treatment. [15][16][17][18][19] While most acupuncture trials have involved acupuncture needling close to the site of pathology, with or without addition of distal or contralateral acupuncture points, many Chinese medical practitioners purely use acupuncture points contralateral to the site of pain to treat unilateral limb pain, such as that arising from the shoulder or leg. 15 20 However, there is little scientific evidence to validate the clinical effects of contralateral acupuncture in morbid subjects, despite there having been several studies in animals and healthy human volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that EA promotes the release of analgesic substances such as opioids [4]. However, more recent work indicated distinct mechanisms of EA analgesia between different stimulating frequencies [4, 7], durations [7, 8], intensities [5, 6, 9], locations [2], and subject conditions (healthy versus pathological states) [13]. Thus, various experimental designs and techniques should be applied in combination towards a comprehensive elucidation of EA mechanisms.…”
Section: Discussionmentioning
confidence: 99%